The Relevance of Kurikulum Merdeka to Al-Ghazali’s Educational Philosophy - Faqih Muhammad; Aris Zaenal Amin; Nurul Mubin (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study was conducted to carry out a more in-depth examination of the relevance of the Merdeka Curriculum to Al-Ghazali's educational philosophy. The study investigates the values embedded within the Merdeka Curriculum and subsequently connects them to Al-Ghazali's educational thought, with the aim of identifying the points of relevance between the two. This research employs a qualitative approach through a library research method, with data analyzed using content analysis. The findings of this study conclude that the educational concepts found in the Merdeka Curriculum are relevant to Al-Ghazali's educational philosophy. First, in terms of educational objectives, both place equal emphasis on character development and moral formation. Second, regarding the characteristics of educators, both position the teacher as a transmitter of knowledge and a living example in daily life. Third, learners are required to be actively engaged in the learning process and to embody noble moral values.